Mathematical modeling methods for estimation the thermophysical properties of heat-protective composite materials - et. al., N.A. Kucheva, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The paper proposes a method of mathematical modeling for the identification of thermophysical properties using the developed software package based on a composite material model, presented as a combination of plates of alternating dissimilar components, of the material of fibers and air, oriented parallel and perpendicular to the heat flow. The influence of the angle of orientation of fibers and their volumetric content on the effective thermal conductivity is established.